The Relationship Between Gadget Addiction and Visual Acuity in Elementary School Student of Mlirip II Mojokerto - Tria Wahyuningrum; Veryudha Eka Prameswari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Technology that is increasingly sophisticated is very influential in human life. Countless types of technology can be found in this modern era. One example of a very popular technology is gadgets. Psychologically, gadgets are easy to create addiction, game facilities that exist in the gadget make children always challenged to reach a higher level. Waste and especially on the eyes that are always used to view gadgets for a long time and without rest can result in asthenopia or tired eyes. Namely, the pupils are slow to react to light, so there is a decrease in visual acuity. The design used in this study is an analytic correlation with cross-sectional approach. The population in this study were all 4-5 graders at Mlirip II Elementary School in Mojokerto. The sampling technique is to use total sampling, that is, the entire population is used as a sample, which is 95 respondents. The results of this study are the fit model, namely the model interpreting the influence between duration, frequency and type of gadget on visual acuity. The duration and frequency of gadget usage significantly affect visual acuity. While for this type of gadget is not significant and does not affect visual acuity. If the duration of gadget usage increases, the decrease in visual acuity ratio increases by 5,299 times. If the frequency of gadget usage increases, the ratio of decreased visual acuity increases by 5,986 times. The level of accuracy of the model in this study was 85.3%. Eye disease problems in children can be prevented by early detection to find out the vision status in children supported by eye examination as a measuring instrument, namely snallen card (Snellen card).